2007
DOI: 10.1002/jcu.20307
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes in the cephalic vein of patients with hemodialysis arteriovenous fistula

Abstract: The increase in cross-sectional area and flow volume of the cephalic vein is larger in patients with brachiocephalic fistulas than in those with radiocephalic fistulas; however, flow velocities and waveform parameters are not different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
5
23
0
Order By: Relevance
“…Blood flow in the cephalic vein is normally approximately 28 ± 14 ml/min [35]. Successful radial-cephalic AVF have flow rates averaging between 600–1000 ml/min with higher peak flows in the larger diameter brachial-cephalic AVF.…”
Section: Mechanisms Contributing To Avf Maturation and Failurementioning
confidence: 99%
“…Blood flow in the cephalic vein is normally approximately 28 ± 14 ml/min [35]. Successful radial-cephalic AVF have flow rates averaging between 600–1000 ml/min with higher peak flows in the larger diameter brachial-cephalic AVF.…”
Section: Mechanisms Contributing To Avf Maturation and Failurementioning
confidence: 99%
“…34 Studies evaluating successful radial-cephalic AVF reveal normal flow rates averaging between 600–1000 ml/min, with many individual AVF exposed to even higher peak flows, and this magnitude of flow increases substantially in the larger diameter brachial-cephalic AVF (Table 2). Dixon et al reported that 90% of forearm AVF have flow between 500–2000 ml/min, whereas 90% of upper arm AVF have flow between 500–3000 ml/min.…”
Section: Flow and Pressurementioning
confidence: 99%
“…Cephalic vein flow rate is normally 28 ml/min for a vein diameter of 2.3 mm [14]. In order to keep the Reynolds number (Re) in our enlarged model of 5 mm diameter similar to its physiological value, the flow rate was adjusted to 60 ml/min (Re = 73).…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The 3D geometry and the meshing were designed using GAMBIT (Fluent Inc.). While the cephalic vein diameter usually ranges from 1.9 -3.9 mm, reaching from 1mm to over 6 mm in actual measurements [14,18,19], we chose a 5 mm inner diameter and 85 mm long straight tube section to make it compatible with the in vitro model in our laboratory. A 16 gauge (1.3 mm inner diameter, 1.7 mm outer diameter) catheter was placed inside the vein with an entrance orientation of 30˚ relative to the vein symmetry axis.…”
Section: Geometry and Computational Meshingmentioning
confidence: 99%